Uji Kualitatif Senyawa Metabolit Sekunder Pada Daun Palado (Agave Angustifolia) Yang Diekstraksi Dengan Pelarut Air Dan Etanol - Ergina, Ergina; Nuryanti, Siti; Pursitasari, Indarini Dwi (Universitas Tadulako, 2014)
Study on qualitative test of secondary metabolites compounds has been done on Palado leaves (Agave angustifolia) extracted in water and ethanol by maceration technique. The aim of this research was to determine the chemical content of Palado leaves. The methode used was phytochemical scrinning (qualitative test) using test tube to determine type of the active compounds contained in the plant. Chemicals tested in this study were alkaloids, terpenoids, steroids, flavonoids, and tannins. Components of Palado leaves extracted in water and ethanol were analysed by colour test using several reagents to determine alkaloids, terpenoids, steroids, flavonoids, and tannins. Specific reagents used in this study interacted with the sample based on the principle of ‘like dissolve like’. The results showed that the water and ethanol extracts of Palado leaves contained alcaloids, flavonoids dan tannins.